Unifying local and large-scale drivers of the Faroe shelf ecosystem - Hátún, Hjálmar; Danielsen, Jóhannis; Olsen, Bergur; Jacobsen, Sólvá; Vang, Helga Bára Mohr; Kristiansen, Inga; Larsen, Karin Margretha H.; Gaard, Eilif; Salter, Ian; Steingrund, Petur; Mork, Kjell Arne (Frontiers in Marine Science, 2025)
Demersal fish stocks and seabird populations on the Faroe shelf have declined profoundly over the past half-century, and the relative role of exploitation and climate remains a key question. The dynamics of the subpolar gyre influences both the marine climate and several ecosystems in the northeastern Atlantic. Furthermore, a more than century old hypothesis suggests that production in marine ecosystems along the eastern margin of the Norwegian Sea is fueled by transport of nutrient- and zooplankton-rich subarctic waters from the Iceland Sea-Jan Mayen region. Recent research has, on the other hand, related the productivity of the Faroe shelf ecosystem to local processes. These contrasting perspectives are here combined, to explain the highly variable recruitment, and thus stock sizes, of Faroese cod (Gadus morhua) and guillemots (Uria aalge). We propose that good recruitment to demersal fish stocks and seabirds requires both high on-shelf biological production and high oceanic food content, proxied by large volumes of subarctic waters surrounding the Faroe shelf.